On directable nondeterministic trapped automata - Imreh, Balázs; Imreh, Csanád; Ito, Masami (Acta Cybernetica, 2003)
A finite automaton is said to be directable if it has an input word, a directing word, which takes it from every state into the same state. For nondeterministic (n.d.) automata, directability can be generalized in several ways. In [8], three such notions, D1-, D2-, and D3-directability, are introduced. In this paper, we introduce the trapped n.d. automata, and for each i = 1,2,3, present lower and upper bounds for the lengths of the shortest Di-directing words of n-state Di-directable trapped n.d. automata. It turns out that for this special class of n.d. automata, better bounds can be found than for the general case, and some of the obtained bounds are sharp.